The effect of Hatha Yoga on pain intensity in severe primary dysmenorrhea among students: A randomized controlled trials - Ignatio Rika Haryono; Jessica Putri Sudarman; Nawanto Agung Prastowo; Lilis Lilis (Alma Ata University Press, 2023)
Background: Yoga has been known as an alternative therapeutic modality for reducing pain. The benefits of yoga for reducing pain have been proven. Women often suffer pain due to dysmenorrhea. The effect of Yoga on dysmenorrhea pain has not been widely studiedObjectives: This study aimed to investigate the effect of hatha yoga on pain in primary dysmenorrhea (PD). Methods: This was a randomized controlled study (RCT) involving 50 female students, 25 each in control (C) and yoga group (Y). PD was diagnosed by Working ability, Location, Intensity (Wong-Baker scale), and Days of the Pain of Dysmenorrhea (WaLIDD) questionnaire. Pain intensity was assessed by the Numeric Rating Scale (NRS). Hatha yoga training was conducted for 12 weeks. The unpaired t-test, ANOVA and Tukey post hoc, and Pearson correlation test was applied. Significance was set at p<0.05. Results: The characteristics between groups were not different. ANOVA indicated the NRS score in control was not changed, while yoga was diminished (p=0.02). Tukey post hoc showed that the second and third NRS were lower than basal NRS (p=0.038 and 0.01, respectively). The third was also lower than the second NRS (p=0.039). The second and the third NRS in yoga were lower than in control (p=0.027 and <0.01, respectively). The second magnitude of change of NRS was significantly different from the first in yoga (1.92 ±2.4 vs. 3.09 ± 2.8, p=0.018). The magnitude of NRS changes in the first (0.06±1.1 vs. 1.92±2.4, p=0.013) and second (0.02 ± 1.6 vs. 3.09 ± 2.8, p= 0.004) in yoga was significantly greater than the control. NRS score was not correlated with age, BMI, and age of menarche. Conclusions: Hatha yoga exercise ameliorate pain intensity in primary dysmenorrhea among female university students.